(untitled) (Italy, 1997)
Contens: Techiniques for the analysis, characterization and conservation of plant genetic resources; analysis, management and exchange of molecular data; techonology transfer and appication in development countries.
Keywords: Plant genetics,Plant molecular biology,Di truyền cây trồng,Mô thực vật